2019
DOI: 10.1159/000504386
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Dual Red Imaging for Endoscopic Hemostasis of Gastric Ulcer Bleeding

Abstract: Dual red imaging (DRI; Red Dichromatic Imaging (RDI)) is a new type of image-enhanced endoscopy composed of two long wavelengths that together can visualize vessels in the deep submucosa of the gastrointestinal wall. We treated a case of gastric ulcer bleeding in which the bleeding point could be clearly visualized using DRI. A 71-year-old man who was taking warfarin for atrial fibrillation noticed tarry stool, entered a state of hypovolemic shock, and underwent emergency esophagogastroduodenoscopy. The proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…The utility of RDI for the identification and management of GI bleeding has been demonstrated in several case reports. 6 , 7 , 8 , 9 In the present study, RDI helped in identification of the bleeding site, enabling prompt hemostasis in 1 attempt in the majority of cases ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 55%
“…The utility of RDI for the identification and management of GI bleeding has been demonstrated in several case reports. 6 , 7 , 8 , 9 In the present study, RDI helped in identification of the bleeding site, enabling prompt hemostasis in 1 attempt in the majority of cases ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 55%
“… 1 Furuichi et al 2 reported that RDI increases the visibility of esophageal varices and red color signs and also predicts the depth of esophageal varices by changing degrees of visibility. Kubosawa et al 3 reported that in the presence of active bleed from a gastric ulcer, the bleeding point was better visualized with DRI and led to prompt hemostasis. DRI is useful in the presence of a spurting hemorrhage from a duodenal ulcer; bleeding point is noted as deep yellow, leading to clear identification of the bleeding point.…”
Section: Discussionmentioning
confidence: 99%
“…Kubosawa et al . 16 and Tanaka et al . 17 reported on the usefulness of RDI in endoscopic hemostasis of gastric and duodenal bleeding, respectively.…”
Section: Principles and Clinical Impact Of Rdimentioning
confidence: 93%